Financial literacy and voluntary savings for retirement: novel causal evidence. Issue 16 (2nd November 2019) - Cupák, Andrej; Kolev, Gueorgui I.; Brokešová, Zuzana
ABSTRACT: We utilise recent Household Finance and Consumption Survey microdata to report first causal effects of financial literacy on voluntary private pension schemes participation for a Central and Eastern European (CEE) country, namely Slovakia. Savings for retirement in the supplementary pension schemes are positively associated with financial literacy after controlling for a set of relevant socio-economic variables. One additional correctly answered financial literacy question leads to a 5.6 percentage points increase in the probability of having a voluntary pension savings plan in our ordinary least squares estimates. The causal impact of financial literacy increases to 19.5 percentage points when we address potential endogeneity problems by novel to the literature instrumental variables.